2018
DOI: 10.3390/catal8080308
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Approach to Chiral β-Nitroalcohols by Enantioselective Alcohol Dehydrogenase-Mediated Reduction of α-Nitroketones

Abstract: Chiral β-nitroalcohols are important building blocks in organic chemistry. The synthetic approach that is based on the enzyme-mediated reduction of α-nitroketones has been scarcely considered. In this work, the use of commercial alcohol dehydrogenases (ADHs) for the reduction of aromatic and aliphatic nitroketones is investigated. High conversions and enantioselectivities can be achieved with two specific ADHs, affording either the (S) or (R)-enantiomer of the corresponding nitroalcohols. The reaction conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Our group recently developed a ketoreductase‐catalyzed stereoselective reduction of α‐nitro ketones to chiral β‐nitro alcohols, which can be easily converted to β‐amino alcohols via the subsequent chemical reduction of the nitro group (Scheme 19). [32] Prior to our study, bioreduction of α‐nitro ketones was scarcely studied, with the only detailed study coming from the Brenna group, who reported the stereoselective reduction of α‐nitro ketones using commercial KREDs affording both enantiomers of β‐nitro alcohols with good‐to‐excellent ee values in most cases [33] . In contrast, the gene/protein sequences of the ketoreductases employed in our work are all publicly available.…”
Section: Creation Of One Stereocenter Through Kred‐catalyzed Reductionmentioning
confidence: 99%
“…Our group recently developed a ketoreductase‐catalyzed stereoselective reduction of α‐nitro ketones to chiral β‐nitro alcohols, which can be easily converted to β‐amino alcohols via the subsequent chemical reduction of the nitro group (Scheme 19). [32] Prior to our study, bioreduction of α‐nitro ketones was scarcely studied, with the only detailed study coming from the Brenna group, who reported the stereoselective reduction of α‐nitro ketones using commercial KREDs affording both enantiomers of β‐nitro alcohols with good‐to‐excellent ee values in most cases [33] . In contrast, the gene/protein sequences of the ketoreductases employed in our work are all publicly available.…”
Section: Creation Of One Stereocenter Through Kred‐catalyzed Reductionmentioning
confidence: 99%
“…Lipase, esterase, halohydrin dehalogenase, and HNL catalyzed retro-Henry reaction are used in the kinetic resolution of a racemic β-nitroalcohol or an epoxide. [12][13][14][15][16] Alcohol dehydrogenase catalyzed asymmetric reduction, [17][18][19][20] and HNL catalyzed nitroaldol reaction [21][22][23][24][25] are the other two routes. Both kinetic resolution and asymmetric reduction requires an additional step of substrate preparation, while the former could provide a maximum 50% theoretical yield.…”
Section: Introductionmentioning
confidence: 99%
“…Tentori et al . (2018) also reported two alcohol dehydrogenases (ADHs) for the reduction of aromatic and aliphatic nitroketone. The enantioselectivities of 62–99% e.e .…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme coupled to an immobilized cofactor recycling partner was utilized for the quantitatively asymmetric reduction of rac-2-phenylpropanal to (R)-2-phenyl-1-propanol with an enantiomeric excess of 71%. Tentori et al (2018) also reported two alcohol dehydrogenases (ADHs) for the reduction of aromatic and aliphatic nitroketone. The enantioselectivities of 62-99% e.e.…”
Section: Introductionmentioning
confidence: 99%